Ethnic and racial comparisons of weight-loss treatment utilization history and outcomes in patients with obesity and binge-eating disorder. (January 2022) - Coffino, Jaime A.; Ivezaj, Valentina; Barnes, Rachel D.; White, Marney A.; Pittman, Brian P.; Grilo, Carlos M.
Abstract: Background: This study examined ethnic/racial differences in reported utilization of weight-loss methods/treatments and weight loss among adults with binge-eating disorder (BED) with co-existing obesity. Methods: Participants were 400 adults (non-Hispanic Black: n = 99, Hispanic: n = 38, non-Hispanic White: n = 263) seeking treatment for BED in Connecticut from 2007 to 2012. Participants were asked about prior weight-loss methods/treatments and resulting weight losses. Results: Overall, self-help diets were utilized most; mental-health services were utilized least. While non-significant differences for most methods/treatments were observed by ethnicity/race, significant differences emerged for self-help diets and supervised programs with non-Hispanic Whites, in general, utilizing these diets more frequently and losing more weight on these types of diets. Conclusions: Among treatment-seeking patients with BED and obesity, non-Hispanic White patients reported histories of greater weight-loss treatment utilization and weight loss than non-White patients for supervised and self-help diets. Findings highlight the need for greater understanding of treatment utilization and outcomes among minority patients with obesity and BED. Highlights: Persons with BED reported on prior weight-loss treatment use and effectiveness. Use of supervised and self-help diets differ by ethnicity/race. Weight lost during supervised and self-help diets differ by ethnicity/race. Results have implications for encouraging culturally relevant weight-loss treatment.